2012
DOI: 10.1002/jqs.2563
|View full text |Cite
|
Sign up to set email alerts
|

Multiproxy record for the last 4500 years from Lake Shkodra (Albania/Montenegro)

Abstract: A multi-proxy record is presented for approximately the last 4500 cal a BP from Lake Shkodra, Albania/\ud \ud Montenegro. Lithological analyses, C/N ratio and d13C of the organic and inorganic carbon component suggest that\ud \ud organic matter and bulk carbonate are predominantly authigenic. The d18O record of bulk carbonate indicates the\ud \ud presence of two prominent wet periods: one at ca. 4300 cal a BP and one at ca. 2500–2000 cal a BP. The latter phase is\ud \ud also found in southern Spain and Central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 49 publications
2
61
0
Order By: Relevance
“…X‐ray diffraction and scanning electron microscopy analyses of the non‐clay fraction indicated that the prominent mineral phase throughout the core is calcite, followed by minor quartz. No aragonite was detected in the samples, indicating negligible amounts of shell fragments (Leone et al ., ; Zanchetta et al ., ). The carbonate fraction is mainly composed of euhedral to subhedral calcite crystals of ca.…”
Section: Resultsmentioning
confidence: 97%
“…X‐ray diffraction and scanning electron microscopy analyses of the non‐clay fraction indicated that the prominent mineral phase throughout the core is calcite, followed by minor quartz. No aragonite was detected in the samples, indicating negligible amounts of shell fragments (Leone et al ., ; Zanchetta et al ., ). The carbonate fraction is mainly composed of euhedral to subhedral calcite crystals of ca.…”
Section: Resultsmentioning
confidence: 97%
“…Multiproxy records (e.g., δ 18 O, pollen, δ 13 C, stable isotopes, etc.) provide a picture of Holocene climatic variability over many areas of Europe including Italy (Magny et al., ; Regattieri, Zanchetta, Drysdale, Isola, Hellstrom, Dallai, ; Zanchetta et al., ). However, less is known about the relationship between climatic variability and soil properties and their influence on prehistory.…”
Section: Resultsmentioning
confidence: 99%
“…Stable isotope records from lake Shkodra (Albania) show the wettest period of the last 4500 cal BP at ca. 2500-2000 cal BP (Zanchetta et al, 2012b). The first two phases of cooling (2600-2000, 1650-1100 cal BP) chronologically comprehend the last two periods of the Calderone glacier expansion (Giraudi et al, 2011).…”
Section: Climate Reconstructionmentioning
confidence: 99%